2009
DOI: 10.1128/jvi.01710-08
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Cysteine 171 of Pestivirus ErnsRNase Prevents Homodimer Formation and Leads to Attenuation of Classical Swine Fever Virus

Abstract: Pestiviruses represent important pathogens of farm animals that have evolved unique strategies and functions to stay within their host populations. E rns , a structural glycoprotein of pestiviruses, exhibits RNase activity and represents a virulence factor of the viruses. E rns forms disulfide linked homodimers that are found in virions and virus-infected cells. Mutation or deletion of cysteine 171, the residue engaged in intermolecular disulfide bond formation, results in loss of dimerization as tested in cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
73
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 58 publications
1
73
0
Order By: Relevance
“…The effective protective immunity elicited by E1Cys24/94v suggests that modified E1 could be used for the development of live-attenuated vaccines. Similar studies have demonstrated that mutation or deletion of Cys171, one out of nine cysteine residues found in CSFV E rns protein that is involved in the formation of homodimers via disulfide bonds, yielded infectious viruses lacking the capability to form homodimers in infected SK6 cells (18). These CSFV E rns mutants were attenuated in pigs and induced a significant neutralizing antibody response in these animals.…”
Section: Discussionmentioning
confidence: 67%
“…The effective protective immunity elicited by E1Cys24/94v suggests that modified E1 could be used for the development of live-attenuated vaccines. Similar studies have demonstrated that mutation or deletion of Cys171, one out of nine cysteine residues found in CSFV E rns protein that is involved in the formation of homodimers via disulfide bonds, yielded infectious viruses lacking the capability to form homodimers in infected SK6 cells (18). These CSFV E rns mutants were attenuated in pigs and induced a significant neutralizing antibody response in these animals.…”
Section: Discussionmentioning
confidence: 67%
“…This is reflected in numerous reports in which mutations of different functional domains in the structural proteins C, E rns , E1, and E2 and in the nonstructural proteins p7 and NS4B were shown to reduce the pathogenicity in pigs, indicating that these genes may be involved in determining CSFV virulence (7,8,9,10,11,12,13,32,36,37,38,39,40,46,54).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the genomes of the GPE Ϫ vaccine virus and the parent ALD virus revealed 225 nucleotide substitutions and 46 amino acid differences (22), which did not provide any conclusive information on the molecular basis of the attenuation. Numerous reports suggest that the viral proteins N pro , C, E rns , E1, E2, p7, and NS4B may be involved in determining the virulence of CSFV in pigs (7,8,9,10,11,12,13,32,36,37,38,39,40,43,46,54). So far, however, all conclusions on CSFV virulence determinants rely on mutations that result in downregulation of pathogenicity.…”
mentioning
confidence: 99%
“…The existence of such naturally occurring viruses and of several engineered virus mutants that lack C171 [90,91] proves that formation of E rns homodimers linked via C171 is not essential for pestivirus viability. Since E rns proteins lacking C171 do no establish dimers stable enough to allow purification and analysis under mild conditions, the formation of stable dimers does not appear necessary for pestivirus viability [91]. Nevertheless, E rns dimerization must have a distinct advantage, because C171 is conserved among the overwhelming majority of pestiviruses.…”
mentioning
confidence: 95%
“…More important, two different CSFV mutants with exchange or deletion of C171 are very significantly attenuated in animals. Therefore, dimer formation seems to be connected with virulence [91].…”
mentioning
confidence: 96%